(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to map the development of literature on the relationship between influencer marketing, parasocial interaction/relationship (PSI/PSR), and consumer trust on social media through a scoping review approach. The study was conducted using the PRISMA-ScR guidelines on articles published between 2021 and 2026, and nine articles met the inclusion criteria. Data were analyzed descriptively through extraction, categorization, and thematic synthesis. The results indicate that influencer credibility, authenticity, expertise, and attractiveness play a significant role in forming parasocial relationships that enhance consumer trust. The study also identified that research is still dominated by the Asian context, focusing on purchase intention, while cross-cultural, longitudinal, and negative impact studies on parasocial relationships are still limited. These findings confirm that authentic emotional connections between influencers and followers are a key factor in building consumer trust in the digital marketing environment